Trade Policy and Democracy for Development in Central African Countries - Gérard, Tchouassi; Honoré, Tékam Oumbé (Journal of Empirical Studies, 2019)
This article shows that trade policy and democracy positively affect economic development. A panel of 11 Central Africa economies with 176 observations from 1995 to 2010 is used to econometrically test this hypothesis. The use of Generalised Least Squares (GLS) shows that there is a link between economic development, captured using Human Development Indicators (HDI), democracy, imports, exports, inflation and regional integration. Inflation and exports negatively affect the well-being of the population. An increase in the inflation rate causes a reduction in purchasing power. An increase in the exports of commodities tends to decrease the quantity of goods available for the country of origin. Imports have a positive effect on HDI probably because this variable tends to increase the quantity of goods available. Imports and democracy have a positive effect on the level of development in Central African countries. The findings are important to policy makers Central Africa who seek to increase trade within, between and with other democratic countries.